Rational High-Throughput System for Screening Emodin High-Yielding Mutant from Marine Strains of Aspergillus flavipes HN4-13 - Lizhi Gong; Zixuan Li; Meina Xu; Yushan Zhou; Wenqing Zhang; Jian Zhao; Xiujuan Xin; Faliang An (Marine Drugs)
Emodin is an anthraquinone compound known for its diverse biological activities, including anti-tumor and anti-inflammatory effects, making it highly applicable in the fields of biology and medicine. The production of emodin using microorganisms represents a sustainable and environmentally friendly approach. A marine-derived Aspergillus flavipes HN4-13 was found to produce emodin, but the yield was too low for industrial production. To develop a high-yielding emodin-producing strain, we established the high-through detection and screening methods of alkaline coloration and deep-well plant culture, enabling the effective selection of high-yielding strains. Following ARTP mutagenesis of the wild strain A. flavipes HN4-13, the resulting mutant strain, M1440, exhibited an increased emodin yield of 124.6 ± 4.95 mg/L. Furthermore, the production of the emodin was enhanced by the exogenous addition of metal ions Mn2+ to the medium. Specifically, the addition of 3 mM Mn2+ resulted in a 133.2% increase in emodin production, with the highest yield reaching 178.6 ± 7.80 mg/L.